Managing Community Home-Based Care Intervention for Children Living with HIV in Jakarta, Indonesia (2009-2024): Role of Social Workers - Simanullang, Gracia V.P.K.; Rachmat, Evadana; Imelda, Johanna Debora; Anggita, Kartika; Irwanto, Irwanto (Indonesian Social Work Consortium (ISWC), 2025)
Children and Adolescents living with HIV and AIDS (CALHIV) are one of the most vulnerable populations, especially those living in underserved and marginal communities. This article presents lessons learned and challenges of a Community Home-Based Care (CHBC) intervention by Lentera Anak Pelangi (LAP). This intervention program was initiated as an extension service during the university’s research for a Harm Reduction Program to prevent HIV infection among injecting drug users (IDUs) managed by the HIV and AIDS Research Center, Atma Jaya Indonesian Catholic University (ARC-AJCUI). LAP was established to respond to community reports about children of IDUs who were neglected by community and families. Since 2009, AJCUI, assisted by government agencies, communities and professionals have supported the children of IDUs who were impacted (affected or infected) by HIV, by advocating their families and communities lacking the right information and education about HIV, and. providing access to resources to fulfill the children’s basic needs and rights. Case file data accumulated over 15 years are presented to highlight LAP journeys as one of the very few HIV community organization providing home-based and multi-disciplinary intervention programs that fills the void in Indonesia’s HIV services and make significant impacts to the lives of CALHIV in Indonesia.